Ai on trial. - Deem, mr mark. warren, mr peter (London, England : Zed Books, 2020)
"With AI now being used in many walks of our every day life, this book looks at the questions surrounding AI and its future. For example: Who owns AI? Is AI a product in its own right? Should AI have rights and responsibilities? What are the status, capacity and authority issues relating to AI? Is AI racist? What are the issues (legal and ethical) created by implicit bias of coders and data sets? Can AI be used to gain a competitive advantage? If so, is it anti-competitive? What is the role of AI in cybersecurity? Can we trust AI? Written by experts and laid out in the style of a trial, starting with opening submissions, followed by the evidence, closing submissions and finally the judgment, the book takes an innovative approach to the most innovative of technological areas."--
PART A - OPENING SUBMISSIONS Chapter 1: What is AI ? and what it is not? Chapter 2: Building blocks Chapter 3: The state of play Chapter 4: Why should AI be placed on trial? PART B - THE EVIDENCE Chapter 5: Owning the errors: who owns the data and the AI? Chapter 6: Data as power: the war to end all wars? Chapter 7: Data as a means of defence: can AI make us cyber secure? Chapter 8: Setting boundaries: do we need a Hippocratic oath? -- Chapter 9: Achieving A diversity: is AI racist? Chapter 10: Gaming the system: using AI to achieve a competitive advantage -- Chapter 11: Out of our hands: should we allow decisions to be entirely automated? Chapter 12: Standing up for the technology: what rights and responsibilities should AI have? Chapter 13: Holding to account: how might causation and liability be established? -- Chapter 14: A question of honour: how can we trust AI? PART C - CLOSING SUBMISSIONS PART D - JUDGMENT
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Artificial intelligence; Artificial intelligence -- Moral and ethical aspects; Law,Technology: general issues,Artificial intelligence; Electronic books